Labour emigration trends in India - Semenikhina, Valeriia (2023)
India is a country with the largest diaspora population in the world with 18 million Indians living outside of their home country and sending the highest remittances back home according to the United Nations report on migration trends from 2020. Most emigrants seek work in other countries and the aim of this thesis is to take a closer look at the relevant trends and patterns of labour emigration from India in the twenty-first century to get a bigger picture about the largest community of migrant workers in the world.